Linking 'omics' to function unlocks the biotech potential of non-model fungi. Issue 14 (April 2019) - Wilken, St. Elmo; Swift, Candice L.; Podolsky, Igor A.; Lankiewicz, Tom S.; Seppälä, Susanna; O'Malley, Michelle A.
Abstract: Nonmodel fungi are increasingly used in biotechnology, spanning medical, industrial, and even agricultural applications. Long-read sequencing technologies have led to a rapid rise in the number of high-quality sequenced fungal genomes and transcriptomes available for study. This information, coupled with bioinformatic analyses, allows access to a striking variety of potential genes to target for downstream characterization and incorporation into bioproduction strategies. However, nonmodel organisms are notoriously difficult to cultivate and genetically modify, limiting the speed at which in silico discoveries can be tested and translated into application. It is critical to combine sequencing information and systems biology to guide both genetic engineering and heterologous expression strategies to harness the biotech potential of nonmodel fungi. This review highlights recent examples where bioinformatics was used to identify genes and pathways of interest that were later exploited to produce biotechnologically important secondary metabolites, transporters, and lignocellulose-active enzymes. We also highlight opportunities where modern approaches, such as genome-scale models and genome editing, may be used to rapidly improve our understanding of nonmodel fungi and fully exploit them for synthetic biology and biotechnology applications. Highlights: More than 1000 non-model fungal genomes have been sequenced to date. Bioinformatic tools are available to analyze sequencing data to find biotechnologically important enzymes and pathways. Direct genetic engineering of non-model fungi is difficult, but emerging techniques are promising. Heterologous expression of fungal genes is a viable alternative to exploit non-model fungi for biotechnology.